PENGARUH SUBSTITUSI FODDER JAGUNG PADA SILASE RUMPUT ALAM TERHADAP KONSUMSI DAN KECERNAAN SERAT, KONSENTRASI VFA DAN KADAR GLUKOSA DARAH PADA PEDET JANTAN SAPI PERSILANGAN ONGOLE X BRAHMAN LEPAS SAPIH (Effect of corn fodder substitution for native.....) - Sefrans Banamtuan; I Gusti Ngurah Jelantik; G. A. Y. Lestari; Imanuel Benu (Universitas Nusa Cendana, 2020)
The objective of this experiment was to evaluate the effect subsitutional of corn fodder on intake and fiber digestibility, volatile fatty acid and blood glucose concentration of weaned Ongole x Brahman calves. This experiment followed a 4x4 latin square design with four treatments, i.e. G : 100% nature grass silage, GCF1 : 35% nature grass silage, 35% corn fodder silage and 30% concentrate, GCF2 : 17,5% nature grass silage, 52,5% corn fodder and 30% concentrate, GCF3 : 70% corn fodder and 30% concentrate. The measured variables included fiber intake and digestibility, volatile fatty acid and blood glucose concentration. Data were subjected to Analysis of Variance (Anova) followed by Duncan Multiple Range Test to separate between means with SPSS 21. Result showed that fiber intake was significantly (P<0.05) lower in GCF3 (299,88 g.d-1) compared to the other treatments which varied between 661,55 to 1293,95 g.d-1. Fiber digestibility, however, did not differ (P>0.05) between treatments, i.e. varied between 55,95 to 72,65%. Volatile Fatty Acid concentration increased (P<0.05) with the increasing levels substitutions of corn fodder in feed. The treatments did not affect (P>0.05) blood glucose concentration of Ongole calves. It can be concluded that substitution of corn fodder for native grass silage has significant effect on fiber intake and Volatile Fatty Acid concentration but not on fiber digestibility and blood glucose concentration of weaned cross Ongole calves.